1989
DOI: 10.1021/j100347a045
|View full text |Cite
|
Sign up to set email alerts
|

Rate constants for reduction of substituted methylperoxyl radicals by ascorbate ions and N,N,N',N'-tetramethyl-p-phenylenediamine

Abstract: Absolute rate constants (k) for reduction of substituted methylperoxyl radicals by ascorbate ions and by TMPD [N,N,-A'.N'-tetramethyl-p-phenylenediamine) in aqueous solutions have been determined by pulse radiolysis. The rate constants vary from 106 to 109 M"1 s'1, increasing as the electron-withdrawing capacity of the substituent on the peroxyl group increases.Linear correlations are observed between log k and the Taft substituent constants * for a wide variety of substituents, but not all substituents fit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 1 publication
2
81
1
Order By: Relevance
“…This nonlinear behavior with respect to Raman spectral intensity motivated the present study of ascorbic acid, C 6 H 8 O 6 or AH 2 .…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…This nonlinear behavior with respect to Raman spectral intensity motivated the present study of ascorbic acid, C 6 H 8 O 6 or AH 2 .…”
Section: Introductionmentioning
confidence: 78%
“…From comparing three different ascorbic-like compounds, assignments of bands due to AH 2 and AH − were made, and it was concluded that the presence of the ring in the structures gave rise to strong signals in the Raman spectra and that signals from the side chains were not nearly as strong. In 1971 Hvoslef and Klaeboe used a red helium-neon laser to study AH 2 as crystals and in aqueous dilution to supplement infrared absorption experiments.…”
Section: Raman Vibrational Spectroscopymentioning
confidence: 99%
See 3 more Smart Citations